Complex diseases and co-morbidities: polycystic ovary syndrome and type 2 diabetes mellitus. Issue 3 (March 2019) - Rodgers, Raymond J; Avery, Jodie C; Moore, Vivienne M; Davies, Michael J; Azziz, Ricardo; Stener-Victorin, Elisabet; Moran, Lisa J; Robertson, Sarah A; Stepto, Nigel K; Norman, Robert J; Teede, Helena J
Abstract : Objective: Many complex diseases exhibit co-morbidities often requiring management by more than one health specialist. We examined cross-speciality issues that ultimately affect the health and wellbeing of patients with polycystic ovary syndrome (PCOS). PCOS was originally described as a reproductive condition but is now recognised to also be a metabolic and psychological condition affecting 8–13% of women of reproductive age. With a four-fold increased risk of type 2 diabetes (DM2), the Population Attributable Risk of DM2 that could be avoided if PCOS were eliminated is a substantial 19–28% of women of reproductive age. To determine the extent to which PCOS is an important consideration in diabetes development, we examined publications, funding, guidelines and predictors of risk of developing DM2. Results: We found that the topic of PCOS appeared in specialist diabetes journals at only 10% the rate seen in endocrinology journals – about 1 in 500 articles. We found research funding to be substantially less than for diabetes and found that diabetes guidelines and predictive tools for DM2 risk mostly ignore PCOS. This is surprising since insulin resistance in women with PCOS has a different aetiology and additionally women with PCOS are at increased risk of becoming overweight or obese – high risk factors for DM2. Conclusions: We consider the causes of these concerning anomalies and discuss current activities to address the co-morbidities of PCOS, including the recent development of international guidelines, an international PCOS awareness program and potentially changing the name of PCOS to better reflect its metabolic consequences.